The Adjunctive Role of Nutritional Therapy in the Management of Phlegmon in Two Children with Crohn’s Disease - Day, Andrew S.; Brown, Stephanie C. (Frontiers in Pediatrics, 2017)
Crohn’s disease may be complicated by the development of penetrating (fistulizing) or structuring complications. The presentation of an intra-abdominal phlegmon or abscess with or without an associated fistula has traditionally required surgical intervention. This series of two cases illustrates a beneficial role of non-surgical management, with parenteral and then enteral nutrition playing central roles. This report further elaborates the potential adjunctive role of enteral nutrition in the management of this complication of CD.